PERILAKU PENGGUNAAN MEDIA SOSIAL DAN IDENTITAS DIRI (Studi Deskriptif Kualitatif Tentang Perilaku Penggunaan Media Sosial dan Identitas Diri di Kalangan Mahasiswa S1 Jurusan Komunikasi Universitas Slamet Riyadi Surakarta) - Aryo Putro, Fanny Hendro (Transformasi, 2017)
Many university students use social media, in the good side it can increse their knowledgeand in the other side can give bad influence such as not appreciate about time and getimpact about what became trens in social media. The existence of social media has becomea part of the pattern of life of students. A little To much will exert influence in the creationof or changes to the identity of users of social media. This research uses qualitativeresearch methods, descriptive phenomenology of approach with research on the method ofphenomenology is to (1) Textural description: what is the subject of research on aphenomenon. (2) Structural description: how the subject experiencing and interpret herexperiences with regard to the utilization of social media among students in aspects of thedevelopment and establishment of self-identity. Some of the views to see all socialrelationships with social media-based internet identity in the formation of a one-semesterstudent is at a cycle of development that are transitional towards a more mature phase.Social media became a staple in the lives of students. Related with undergraduate studentidentity in the Department of Communication Sciences of Slamet Riyadi University in theuse of social media, that the media usage is more adapted to the mood. Also in thepresence of the use pseudonyms in the account he had made indicating that the student hasnot had a sense of responsibility that is full of what has been written and upload content.Then required the existence of a form of parapet as separator changes behavior offered bysocial media.Keywords: student’s identity, usage behavior of social media, social media